Bullying victimization and suicidal ideation among Chinese adolescents: a moderated mediation model of depressive symptoms and perceived family economic strain - Xiaoyu Jiang; Qiaoyue Wei; Wenwen Yin; Shuibo Pan; Chenyangzi Dai; Linhua Zhou; Chunyan Wang; Xiujin Lin; Junduan Wu (BMC Public Health)
Abstract Background There is substantial evidence linking bullying victimization to suicidal ideation, but the mechanism behind this link is not well understood. This study investigates whether depressive symptoms mediate the relationship between bullying victimization and suicidal ideation, and whether perceived family economic strain moderates this mediation. Methods Data were collected from 7,702 adolescents (mean age = 14.74 ± 1.69 years, 52% girls) using a self-report questionnaire that assessed bullying victimization, depressive symptoms, suicidal ideation and perceived family economic strain. Mediation and moderated mediation analyses were conducted using the PROCESS macro in SPSS. Results Suicidal ideation was significantly associated with both bullying victimization and depressive symptoms, as determined by linear regression analysis (both p < 0.001). The relationship between bullying victimization and suicidal ideation was partially mediated by depressive symptoms, accounting for 66.74% of the effect. Additionally, perceived family economic strain could moderate the link between bullying victimization and depressive symptoms (β=-0.017, p < 0.001), indicating that increased perceived family economic strain attenuates the impact of bullying victimization on depressive symptoms. Conclusion Our research affirms bullying victimization substantial influence on adolescent suicidal ideation, with depressive symptoms mediating this link. The study also reveals that perceived family economic strain moderates this relationship, indicating the necessity for interventions that address both psychological and economic factors to holistically support the mental health of bullied adolescents.